Development of Nano‐Al Based Highly Metalized Fuel‐Rich Propellant for Water Ramjet Propulsion Applications. Issue 7 (13th March 2020) - Ramakrishnan, Murugesan; Chakravarthy, Satyanarayanan R.; Kandasamy, Jayaraman; Sarathi, Ramanujam
Abstract: Aluminium‐water reaction‐based ramjet propulsion system shows the higher theoretical performance when compared to the conventional solid propellant based propulsion system for high‐speed underwater applications. In the present study, investigations have been carried out on water ramjet propulsive performance using theoretical approach and also the primary combustion characteristics of the fuel‐rich propellant compositions studied experimentally. The aluminized fuel‐rich propellant compositions contain 40–50 % of aluminium with the average particle sizes of 18 μm, 250 nm, and 100 nm, and also comprise 34.5‐46 % of Ammonium Perchlorate (AP) in a total of 15 formulations, are tested over a pressure range of 0.2–3.1 MPa in CO2 atmosphere. Paraffin wax and Hydroxyl‐terminated Polybutadiene (HTPB) based binders are used for the preparation of the nano and micro aluminized propellants respectively. Primary combustion features are estimated using thermochemical calculation for the fuel‐rich propellants. The calculations show that the increase of metal fraction from 40–60 % in the composition leads to a marginal decrement in the combustion temperature whereas it favors the formation of a large fraction of condensed phase products and the presence of unreacted metals also increases considerably. Theoretical propulsive performance calculations show that higher Isp is ascertained with the higher metal content in the fuel‐rich propellants. By comparing with Magnesium (Mg) and Aluminium (Al) based propellants, a water ramjet‐powered using Boron (B)‐based propellant shows higher theoretical specific impulse for a ratio of water to fuel greater than 1. The primary combustion of propellants comprises 50 % aluminium by mass and causes more than 20 % of mass to leave as residue, which mainly contains unreacted aluminium, besides other condensed phase combustion products. Nano aluminized propellant compositions show a 2–5 times higher burning rate than the micro aluminized counterparts. These propellants exhibit a wide range of pressure indices (n) from 0.23 to 0.56. Morphology and elemental composition of condensed phase combustion products from primary combustion are also examined. Abstract :